IMPLEMENTASI SISTEM PENUNJANG KEPUTUSAN PENILAIAN KUALITAS KARYAWAN TERBAIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA RIZKY SERVICE TJOMPUTER - Firdaus Hajiyansah; Muhammad Afif Alrasyid; Sulistia Herti Riana; Hendra Tafonao; Saprudin (CV. Multi Kreasi Media, 2024)
Rizky Service tJomputer is a business engaged in computer and laptop repair services. Founded by Rizky Hanifudin in 2018, this business is located at Kebonsalak, RT 04/RW 01, Purwosari, Kranggan District, Temanggung Regency, Central Java 56271. Rizky Service tJomputer caters to various technical needs of computers and laptops, including reinstallations, device damage analysis, operating system installations, application installations, hardware repairs, component upgrades, and technical consultations. Evaluating the performance of technicians is one of the main focuses to improve service quality and customer satisfaction. Currently, the performance appraisal system at Rizky Service tJomputer is still done manually and subjectively. To increase objectivity, this study proposes a decision support system (DSS) based on 360 Degree Feedback and Simple Additive Weighting (SAW). The 360 Degree Feedback method is very suitable because it involves assessments from multiple perspectives, namely customers, fellow technicians, and self-assessment. Meanwhile, the SAW method is used for a weighted summation method that seeks the weighted sum of performance ratings on each alternative for all attributes, such as service speed, work quality, and customer satisfaction levels. The Simple Additive Weighting (SAW) method is an effective and easy-to-use tool in decision support systems (DSS) to evaluate various alternatives based on several criteria. With this method, we can sum up the weighted values of each criterion to obtain a total score used in the ranking of alternatives. This method is suitable for use in various situations, including employee assessment, product selection, and project evaluation.